Analisis Butir Soal Ujian Sekolah/Madrasah Matematika SD/MI Tahun Ajaran 2015/2016 Berdasarkan Domain Isi dan Domain Kognitif TIMSS - Faizah, Indah Nurul, Prof. Dr. Budi Murtiyasa, M.Kom (2017)
TIMSS (Trends in International Mathematics and Science Study) is an international survey to know ability of student in mathematics and science internationally. Indonesia has followed international study of TIMSS since 1999 but ranks Indonesia in TIMSS reside in low category. This research aim to know composition of content domain and cognitive domain at elementary school test problem 2015/2016 at mathematics subject based on content domain and cognitive domain of TIMSS. Source of research data is elementary school test problem document 2015 / 2016 mathematics subject. This research is a qualitative research with content analyze method. This research was conducted to know content of content domain and cognitive domain in each problem item. Percentage Result of from research of content domain at test item there are 37,5% for the number, 45% for measurement and geometry, and 17,5% presentation of data.. Percentage of cognitive domain at test item that is 40% for cognitive domain of knowing, 50% applying and 10 % reasoning. Keywords: Content domain, Cognitive domain, TIMSS, Math exam